Nanostructured tin oxide: synthesis and gas-sensing properties - Niranjan, R. S.; Hwang, Young Kyu; Kim, D. K.; Jhung, S. H.; Chang, J. S.; Mulla, Imtiaz S. (Materials Chemistry and Physics, 2005)
Pure and Ru-doped nanostructured SnO2 sensing materials were synthesized using a modified Pechini route. Incorporation of Ru in SnO2 results in the reduction of particle size (8.3 nm) compared with that of the pure SnO2 (28.2 nm). Moreover, the sensor exhibited a reasonably good sensitivity towards both H-2 and liquified petroleum gas (LPG). The effect of Ru incorporation, operating temperature, and gas concentration on the structure, morphology, and sensitivity is discussed using the results of X-ray diffraction (XRD), and scanning electron microscopy (SEM) along with sensing performance. © 2005 Elsevier B.V. All rights reserved.
Keywords: hydrogen and hydrocarbon sensor; Nanostructure; ruthenium; tin oxide

Investigations on Ru doped ZnO: strain calculations and gas sensing study - Navale, Shalaka C.; Ravi, V.; Mulla, Imtiaz S. (Sensors and Actuators B-Chemical, 2009)
Pure and ruthenium (Ru) doped nano-crystalline zinc oxide (ZnO) powders were synthesized by using well-known citrate gel route. Citric acid acts as a chelating agent and thus helps in the formation of nanoparticles. The detailed X-ray diffraction (XRD) studies using Hall equation reveal that in the nanoscale dimensions, incorporation of Ru modulates the lattice strain. It is interesting to note that on Ru doping, the compressive strain present in the undoped ZnO changes into tensile strain. We have tested the response of these specimens individually for reducing gases like H(2), LPG (liquefied petroleum gas), C(2)H(5)OH (ethanol), CO, acetone and oxidizing gases like NO, and Cl(2). Undoped ZnO responses perceptibly to LPG while Ru doped sample highly senses ethanol vapors. This might be due to either change in composition on Ru doping or/and difference between basicity of LPG and C(2)H(5)OH vapors. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Citrate gel; Ethanol sensor; LPG sensor; Nanomaterials; ruthenium